2006
DOI: 10.1128/jb.188.9.3412-3414.2006
|View full text |Cite
|
Sign up to set email alerts
|

Protein Splicing of SufB Is Crucial for the Functionality of the Mycobacterium tuberculosis SUF Machinery

Abstract: The SufBCD complex is an essential component of the SUF machinery of [Fe-S] cluster biogenesis in many organisms. We show here that in Mycobacterium tuberculosis the formation of this complex is dependent on the protein splicing of SufB, suggesting that this process is a potential new target for antituberculous drugs.The worldwide recrudescence of tuberculosis has been associated with the emergence of multidrug-resistant strains of Mycobacterium tuberculosis, its causative agent. This alarming situation has re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 16 publications
(17 reference statements)
0
29
0
Order By: Relevance
“…The locus in the bacteria analysed consists of mptB which has in C. glutamicum the locus tag NCgl1505 and in M. tuberculosis Rv1459c. sufR encodes a transcriptional regulator in front of an operon of the SUF machinery of [Fe-S] cluster synthesis ( Huet et al ., 2006 ). The genomic region displayed encompasses 7 kb, and orthologous genes are highlighted accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…The locus in the bacteria analysed consists of mptB which has in C. glutamicum the locus tag NCgl1505 and in M. tuberculosis Rv1459c. sufR encodes a transcriptional regulator in front of an operon of the SUF machinery of [Fe-S] cluster synthesis ( Huet et al ., 2006 ). The genomic region displayed encompasses 7 kb, and orthologous genes are highlighted accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…(Noren et al , 2000) It was shown that unspliced SufB is non-functional because it fails to associate with SufC or SufD by yeast two-hybrid assay. (Huet et al , 2006) These preliminary studies indicate that the Suf pathway and/or intein splicing may be good targets for novel antibiotic therapy to treat drug-resistant TB. Future studies are required to elucidate the biochemical functions of the novel Suf proteins present in Mycobacteria .…”
Section: The Importance Of Suf In Human Pathogens: Tuberculosis Anmentioning
confidence: 97%
“…Unspliced SufB cannot interact with other components in the SUF system and is inactive during iron-sulfur cluster protein assembly. Thus, SufB maturation is an interesting target for inhibitors to block iron sulfur cluster biosynthesis in M. tuberculosis [279–281]. …”
Section: Biosynthesis Of Iron-sulfur Clustermentioning
confidence: 99%